Effects of Exercise Frequency and Intensity on Reducing Depressive Symptoms in Older Adults With Insomnia: A Pilot Randomized Controlled Trial - Chin, Edwin C.; Yu, Angus P.; Leung, Chit K.; Bernal, Joshua D.; Au, Whitney W.; Fong, Daniel Y.; Cheng, Calvin P.; Siu, Parco M. (Frontiers in Physiology, 2022)
Background: The effects of exercise frequency and intensity on alleviating depressive symptoms in older adults with insomnia are unclear. Purpose: To investigate the influence of different exercise frequencies and intensities on prescribed aerobic-type physical activity (i.e., 75 minutes of vigorous- or 150 minutes of moderate-intensity exercise weekly) for reducing depressive symptoms in older adults living with insomnia as recommended by the World Health Organization. Design: Randomized, controlled, assessor-blinded trail. Setting: A single research site in Hong Kong. Participants: Older adults age 50 years or older with depressive symptoms and insomnia. Intervention: Participants were randomly assigned in a 1:1:1:1:1 ratio to the following groups: attention control (CON), moderate walking once weekly (MOD×1/wk), moderate walking thrice weekly (MOD×3/wk), vigorous walking once weekly (VIG×1/wk), and vigorous walking thrice weekly (VIG×3/wk). The total weekly exercise volumes among the walking groups were matched to the minimum recommended physical activity volume. Measurements: Depression, anxiety, self-perceived sleep quality, insomnia severity, actigraphy-assessed 7-day sleep data, 7-day sleep diary, cardiorespiratory fitness, adherence, and habitual physical activity were examined at baseline and after 12 weeks of intervention. Results: Both MOD×3/wk and VIG×3/wk groups demonstrated reduced depression (Hospital Anxiety and Depression Scale – Depression: MOD×3/wk: -68.6%; VIG×3/wk: -67.4%) and anxiety levels (Hospital Anxiety and Depression Scale – Anxiety: MOD×3/wk: -54.3%; VIG×3/wk: -59.8%) compared with CON (both p<0.01). Self-perceived sleep quality was improved in MOD×3/wk (-31.4% of Pittsburgh Sleep Quality Index, PSQI), VIG×1/wk (-34.1% of PSQI), and VIG×3/wk (-38.3% of PSQI), but not in MOD×1/wk, when compared with CON (p<0.05). No serious adverse events were observed in this study. Conclusion: The effects of walking training on reducing depressive symptoms appeared to be dependent on exercise frequency. Our findings suggest that three sessions of walking per week at either moderate or vigorous intensity are effectively alleviates depressive symptoms in older adults with insomnia. Additional research is needed to further verify the effects of exercise frequency on depression.